2008
DOI: 10.2460/ajvr.69.12.1615
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of induction of porcine dermatitis and nephropathy syndrome in gnotobiotic pigs with negative results for porcine circovirus type 2

Abstract: These data suggested that PDNS is a manifestation of disseminated intravascular coagulation in swine. For the experimental conditions reported here, combined infection with g1-TTV and PRRSV was implicated in the genesis of these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 33 publications
0
55
0
2
Order By: Relevance
“…Attempts to reproduce PDNS experimentally with PCV2 have been unsuccessful; however, PDNS has been reproduced experimentally in the absence of PCV2 with PRRSV and a tissue homogenate containing TTV (28). Relatively little is known about the clinical significance of TTV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to reproduce PDNS experimentally with PCV2 have been unsuccessful; however, PDNS has been reproduced experimentally in the absence of PCV2 with PRRSV and a tissue homogenate containing TTV (28). Relatively little is known about the clinical significance of TTV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of this systemic vasculitis, as well as the fibrinous glomerulonephritis, is thought to be immune complex mediated. Importantly, PDNS has been reproduced experimentally without PCV2 by using PRRSV and a tissue homogenate containing torque teno virus (TTV) (28).…”
mentioning
confidence: 99%
“…First evidence highlighted the high prevalence of TTSuV2 infection in postweaning multisystemic syndrome (PMWS), although in most cases, such co-infection does not lead to a disease; however, it is subclinical, suggesting that the disease association is possibly a matter of viral load [66]. Recent reports showed that porcine TTV partially contributed to inducing porcine reproductive and respiratory syndrome, porcine dermatitis and nephropathy syndrome, and hepatitis [82,83]. The latest research indicating that TTSuV2 but not TTSuV1 seems to benefit from the host's disease status suggests that TTSuVs may act as triggers for diseases that cause immune system impairment.…”
Section: Innocent Bystanders or Something Else?mentioning
confidence: 99%
“…4 Both TTV-1 and -2 have been implicated by some authors as another virus that facilitates PCV-2-induced systemic disease. 9,20 Lesions of porcine dermatitis and nephropathy syndrome were detected in pigs with combined experimental infection with TTV and PRRSV, 24 and there may be a relationship between TTV-2 infection and reproductive failure in sows. 47 Other studies demonstrated that pigs with PCVAD were similarly more likely infected with TTV-2 than nonaffected pigs.…”
Section: Discussionmentioning
confidence: 99%